A comparison of back-end frameworks for web application development - Kaluža, Marin (Array, 2019)
Web applications have a complex structure, and for more efficient and faster writing of original program code, frameworks are often used. There are numerous different frameworks on the market that are used to build different parts of software architecture. Only back-end frameworks for web applications development are analyzed. Previous research on evaluation criteria for back-end frameworks, and various sources which by various reasons, represent the list of popularity of back-end frameworks are shown. The framework selection procedure is described, and the reasons of framework selection (Laravel, Rails, Django and Spring) for the analysis are given. The examination (verification) and evaluation of the degree of satisfaction of the selected basic and additional comparison criteria in selected frameworks are carried out. The analysis shows insignificant differences in the overall ratings of analyzed frameworks according to the basic comparison criteria. According to the additional comparison criteria, the analysis shows significant differences in the overall ratings of analyzed frameworks. It is shown that the Django framework, because it is suitable for development of larger applications, suitable for beginner developers, and achieves the highest overall rating of additional comparison criteria, is the best choice of analyzed back-end frameworks for web application development.